Distribution of elastic strain in a pearlite structure - Koga, Norimitsu; Nakada, Nobuo; Tsuchiyama, Toshihiro; Takaki, Setsuo; Ojima, Mayumi; Adachi, Yoshitaka (Scripta materialia, 2012)
Elastic strain and its distribution in a pearlite structure were visualized by means of the electron backscatter diffraction/Wilkinson method. It was found that pearlite colonies have different types of strain fields. Several mechanisms for elastic strain generation were discussed, and it was concluded that the elastic strain is mainly generated because of the lattice misfit between ferrite and cementite at the temperature at which pearlite transformation takes place.